DIASPORIC PERCEPTIONS IN CHITRA BANERJEE DIVAKARUNI'S THE MISTRESS OF SPICES (International Journal of Food and Nutritional Sciences, 2023)
The experiences of those who have moved to other nations provide the basis for diaspora consciousness. Identity crises, homesickness and alienation, displacement, and intercultural disputes are a few examples